การจัดการพลังงานของระบบอัดอากาศ ในโรงงานอุตสาหกรรมผลิตขวดแก้ว - ฟักแสง อัจฉราภรณ์; ยงเจริญ วิทยา (JOURNAL OF SOUTHERN TECHNOLOGY, 2015)
งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาแนวทางในการประหยัดพลังงานลมอัดในอุตสาหกรรมผลิตขวดแก้ว แห่งหนึ่งในประเทศไทย โดยเก็บข้อมูลการใช้งานเครื่องอัดอากาศและสํารวจลมรั่วในระบบอัดอากาศของ โรงงานตัวอย่าง เพื่อหาสมรรถนะของเครื่องอัดอากาศแต่ละเครื่อง รวมถึงการหามาตรการการประหยัดพลังงาน จากการสํารวจการใช้งานของเครื่องอัดอากาศพบว่าเครื่องอัดอากาศส่วนใหญ่มีอายุการใช้งานมากและ มีประสิทธิภาพต่ําโดยมีค่าการใช้พลังงานมากที่สุด คือ 0.446 kW/l/sec และ น้อยที่สุด คือ 0.304 kW/l/sec จึงได้เสนอ 3 มาตรการประหยัดพลังงานคือ (1) การจัดการทํางานของเครื่องอัดอากาศโดยให้เครื่องอัดอากาศ ที่มีสมรรถนะสูงทํางานก่อน ส่วนที่มีสมรรถนะต่ําเก็บไว้เป็นเครื่องสํารอง (2) มาตรการเปลี่ยนเครื่องอัดอากาศ ที่มีประสิทธิภาพสูงมาแทนเครื่องอัดอากาศที่มีสมรรถนะต่ําสุด จากการวิเคราะห์ด้านการเงิน พบว่า ระยะเวลา การคืนทุนอยู่ที่ 4 ปี 9 เดือน มีค่ามูลค่าปัจจุบันสุทธิ 3,914,792 บาท และ มีค่าอัตราผลตอบแทน 21% และ (3) การบํารุงรักษาระบบเครื่องอัดอากาศโดยการซ่อมรูรั่วขนาดใหญ่จํานวน 3 จุดซึ่งจะลดค่าใช้จ่ายได้ถึง 206,256 บาท/ปี Energy Management of the Compressed Air System in Glass Industry The objective of this research was to study energy management of the compressed air system of glass industry in Thailand. Air compressor operation was surveyed in a sample factory to find the performance of each air compressor. In addition the air leakage from the compressed air system was also investigated for energy saving purpose. The results from surveying of the air compressor operation showed that most air compressors were not only old but also had low efficiency. The highest and lowest specific consumption were 0.446 kw/l/sec and 0.304 kw/l/sec, respectively. Thus, three measures of energy saving were proposed. First, machine operation management, the high efficient compressors should run first and the low efficient compressors were alternatives. Second, machine replacement, replace the low efficient compressor with the one that showed higher efficiency. The financial analysis showed that the payback period was 4 years 9 months, the net present value was 3,914,792 Baht and the internal rate of return was 21%. Third, inspection and maintenance, three points of air leakage were found. The estimated saving cost was 206,256 baht/year if the problem was solved.